Strategi Komunikasi CSR Samsung untuk Meningkatkan Pendidikan di Indonesia melalui Program Samsung Innovation Campus (SIC) - LPS, Ennita (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
In Indonesia, one of the challenges experienced by the government here is that there are still many unemployed people. According to data from BPS in August 2022, the unemployment rate in Indonesia was mostly from vocational school graduates, namely 9.42%, 8.57% from high school graduates, 4.59% from Diploma I/II/III graduates and graduates from university is 4.8%. This shows that existing job offers can’t be absorbed by the existing group of educational graduates. To be part of a good corporate citizen in Indonesia, Samsung through its CSR program focuses on education program. Samsung Innovation Campus (SIC), a program through technology skills training to prepare Indonesia's young generation for the digital era with coding and programming and IoT training for senior high school, and vocational high school students. The program is aiming to equip youth with digital literacy including critical technical skills, and bridging educational divides to give underserved students.